Association of High Blood Pressure with Elevated Oxidative Stress, Inflammatory Marker and Albuminuria in Chronic Kidney Disease Patients - Thaha, Mochammad; Kadariswantiningsih, Ika N; Empitu, Maulana A (Journal of Medicine, 2019)
Background: Activation of renin-Angiotensin system in hypertension was believed to be major determinant in endothelial dysfunction, micro-inflammation, and reactive oxygen species generation. This study aimed to investigate the interaction of increased blood pressure with cardiovascular risk factors in chronic kidney disease (CKD). Materials & methods: The study was an observational study with cross-sectional design that consecutively enrolled CKD patients in Universitas Airlangga Hospital and two other hospitals in Surabaya, Indonesia. The resting blood pressure and kidney functions of the participants were examined. Malondialdehyde (MDA) and total antioxidant capacity (TAC) was measured in serum and used as oxidative stress markers. Serum hs-C-reactive protein (CRP), lymphocyte-to-monocyte ratio and platelet-to-lymphocyte ratio were utilized as inflammatory markers, while urine albumin-to-creatinine ratio (ACR) was used as renal disease marker. The participants were grouped based on their systolic and diastolic blood pressure (SBP and DBP). The difference of marker levels between groups was tested using Mann-Whitney test. The correlation between SBP and DBP with inflammation, oxidative stress, and albuminuria was determined using Spearman’s test. Results: As many as 71 patients with CKD were enrolled in this study. As much as 37% of the participants had high SBP and 14% had high DBP. High SBP positively associated with MDA (P<0.05), hs-CRP (P<0.05), platelet-to-lymphocyte ratio (P<0.05), and ACR (P<0.0001) and negatively with lymphocyte-to-monocyte ratio (P<0.05) and TAC (P<0.0001). High DBP associated positively with ACR (P<0.05) and negatively with TAC (P<0.05). Conclusions: High systolic or diastolic blood pressure was significantly associated with inflammation, oxidative stress and albuminuria. Optimal blood pressure control may be one of strategies to prevent inflammation and oxidative stress among CKD patients. J MEDICINE JUL 2019; 20 (1) : 12-18